Administrative Responsibility of Notaries in Making Franchise Agreement Deeds That Have Not Been Registered with the Ministry of Trade - Alyaziza Aisya; M. Sudirman; Benny Djaja (Journal of Social Research, 2025)
Franchise agreements are modern business contracts that carry legal implications based on the principle of freedom of contract in the Civil Code, as well as administrative provisions such as registration with the Ministry of Trade, regulated under Minister of Trade Regulation No. 71 of 2019 on Franchise Implementation. Notaries play a critical role in formalizing these agreements through authentic deeds. However, issues arise when franchise agreements are made without a Franchise Registration Certificate (STPW). While notaries can still create deeds based on the parties' will, they are obligated to provide a legal explanation regarding the administrative status and associated risks. This research employs a normative legal methodology using both legislative and conceptual approaches, with qualitative analysis of legal documents and regulations. The study aims to highlight the significance of franchise agreement registration and the notary’s role in ensuring legal clarity. The findings suggest that notaries should be proactive in informing parties about the legal risks involved when a franchise agreement lacks an STPW, thereby enhancing legal protection for all parties. This research provides recommendations for both notaries and the government to strengthen the understanding of administrative obligations in franchise agreements and ensure better legal safeguards.